Proceedings at the presentation to the Hon. Robert Dale Owen of a silver pitcher, on behalf of the women of Indiana, on the 28th day of May, 1851. - Stone, Lucy, 1818-1893; Catt, Carrie Chapman, 1859-1947; National American Woman Suffrage Association Collection (Library of Congress) (New Albany, Ind., Kent & Norman, printers, 1851)
In 1851, Indiana adopted a state constitution that included a measure protecting the property rights of married women. Robert Dale Owen was the chief architect of this provision and the women of Indiana honored him with a silver pitcher. This pamphlet details the ceremony surrounding this presentation, including speeches by Professor W.C. Larrabee of Indian Asbury University and Robert Dale Owen. What is interesting here is the very narrow way in which the women define their role in society and their prosition vis-a-vis women's rights.
Also available in digital form on the Library of Congress Web site.
Keywords: Women -- Legal status, laws, etc; Owen, Robert Dale, -- 1801-1877.